1998
DOI: 10.1111/j.1469-7793.1998.185bu.x
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating pyramid to horizontal oriens‐alveus interneurone inputs: dual intracellular recordings in slices of rat hippocampus

Abstract: In adult rat hippocampal slices, simultaneous intracellular recordings from pyramidal cells in CA1 and interneurones near the stratum oriens‐alveus border revealed excitatory connections that displayed facilitation on repetitive activation in twelve of thirty‐six pairs tested. Postsynaptic interneurones were classified as horizontal oriens‐alveus interneurones by the pronounced ‘sag’ in response to hyperpolarizing current injection, high levels of spontaneous synaptic activity and by the morphology of their so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
149
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(165 citation statements)
references
References 41 publications
16
149
0
Order By: Relevance
“…The somatostatin-positive interneurons are interesting candidates for governing the time window in which oscillatory activity can take place. Because of the large convergence of many pyramidal cells onto somatostatin-positive interneurons (Ali and Thomson, 1998), these interneurons might sense the electrical activity of a large ensemble of pyramidal cells.…”
Section: Discussionmentioning
confidence: 99%
“…The somatostatin-positive interneurons are interesting candidates for governing the time window in which oscillatory activity can take place. Because of the large convergence of many pyramidal cells onto somatostatin-positive interneurons (Ali and Thomson, 1998), these interneurons might sense the electrical activity of a large ensemble of pyramidal cells.…”
Section: Discussionmentioning
confidence: 99%
“…They have the soma and horizontal dendrites localized in stratum oriens and the axons targeting distal dendrites of CA1 pyramidal cells in stratum-lacunosum moleculare (Lacaille et al, 1987;Ali and Thomson, 1998;Maccaferri et al, 2000;Maccaferri, 2005). These neurons participate in hippocampal theta activity in vivo (Buzsáki, 2002;Klausberger et al, 2003) and in vitro (Pike et al, 2000;Gillies et al, 2002;Hájos et al, 2004;Gloveli et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We focused on somatostatin-expressing stratum oriens interneurons and in particular on O-LM cells, the predominant horizontal cell type in the CA1 hippocampal area (Ali and Thomson, 1998;Maccaferri, 2005), because these cells exhibit intrinsic resonance and spike transfer frequency preference in the theta range (Pike et al, 2000) and have been shown to contribute to the generation of the theta rhythm in vivo (Klausberger et al, 2003). To target this subpopulation, we used transgenic mice expressing enhanced green fluorescent protein (EGFP) in a subset of somatostatin-containing interneurons that mostly comprise O-LM cells in the CA1 stratum oriens (Oliva et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that short-term plasticity is accompanied by changes in P r (for review, see Thomson, 2000;Zucker and Regehr, 2002); however, whether alterations in P r (purely presynaptic) fully account for such plasticity (Gulyas et al, 1993;Paulsen and Heggelund, 1994;Stevens and Wang, 1995;Hanse and Gustafsson, 2001;Silver et al, 2003;Lawrence et al, 2004) or whether postsynaptic alterations also occur (Otis et al, 1996;Rozov and Burnashev, 1999;Oleskevich et al, 2000;Oertner et al, 2002;Harrison and Jahr, 2003) is still a question of active debate. To determine the quantal parameters and the locus of alterations during short-term facilitation at cortical glutamatergic synapses, we took advantage of the robust facilitation of synapses made by hippocampal CA1 pyramidal cells (PCs) onto specific subtypes of interneurons (Ali and Thomson, 1998;Scanziani et al, 1998;Losonczy et al, 2002). Because this facilitation is accompanied by a large change in P r (Ali and Thomson, 1998), we could study this connection under physiologically relevant but highly diverse P r conditions.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the quantal parameters and the locus of alterations during short-term facilitation at cortical glutamatergic synapses, we took advantage of the robust facilitation of synapses made by hippocampal CA1 pyramidal cells (PCs) onto specific subtypes of interneurons (Ali and Thomson, 1998;Scanziani et al, 1998;Losonczy et al, 2002). Because this facilitation is accompanied by a large change in P r (Ali and Thomson, 1998), we could study this connection under physiologically relevant but highly diverse P r conditions. Our results demonstrate a sole presynaptic change during short-term facilitation and are consistent with the "one-release site, one-vesicle" hypothesis.…”
Section: Introductionmentioning
confidence: 99%